In perpetuity ebook - Hoey, Maria (In Perpetuity., 2024)
It’s a surreal smuggling operation across the boundaries of life and death in the latest moody mystery from award-winning graphic novelists Peter & Maria Hoey. The Afterlife is just as the ancient Greeks imagined: an endless twilight where time stands still in perpetuity and shades have nowhere to go. For Jim, that means long shifts at a gas station, with only crossword puzzles and cigarettes to break the tedium. One day, two criminal shades from Jim’s past come to collect a debt. They’ve tracked him down for something he didn’t know he had: the ability to cross back into the living world. It’s a rare gift, and they intend to exploit it. During Jim’s first crossing back into sunny California, he meets Olivia, who is dying on an Echo Park sidewalk. Pulling her back from the edge of death, he strikes a connection that will run deeper than either can imagine. Jim weaves back and forth between the Afterlife and Los Angeles, desperately trying to evade the criminals’ plot. But he and Olivia are pulled into a web of deceit and murder that reaches across both L.A. and the A.L., and ultimately to Hades himself. With a heady blend of film noir and Greek mythology, In Perpetuity reveals both the human capacity for self-deception and the endurance of love.